The Role of Employability Skills and University Support towards Employability: A Mediation of Self-efficacy - Ngoc, Vu Thi Bich; Lan, Pham Thi; Nhi, Nguyen Van; Hanh, Duong Thi My; Yen, Ngo Thi Hai (American Journal of Business Science Philosophy, 2024)
The study aims to delve into the factors influencing self-perceived employability among university students in Vietnam, while also scrutinizing potential gender disparities in these determinants. Employing a cross-sectional design, the research employs structural equation modeling to analyze data gathered from 306 students across various academic disciplines. The study evaluates constructs including perception of employability skills, perception of university support, self-efficacy, and self-perception of employability. Furthermore, a multigroup analysis is conducted to discern any variations in the relationships between these constructs across genders. Results from the structural equation modeling unveil noteworthy gender differences in these relationships. Specifically, while the perception of employability skills significantly impacts the self-perception of employability among males, self-efficacy emerges as a more influential predictor among females. Additionally, the multigroup analysis suggests that the influence of perception of university support on self-perception of employability remains consistent across genders. Nonetheless, a slight gender discrepancy is observed in the relationship between perception of employability skills and self-efficacy, prompting further exploration. These findings illuminate the intricate interplay of employability-related factors and gender in shaping students' perceptions of their employability. The study advocates for tailored interventions that account for these genderspecific influences to enhance employability outcomes among university students
Keywords: employability; employability skills; self-efficacy; Vietnam